Neutrino astronomy current status, future prospects - Gaisser, Thomas K.; Karle, Albrecht (World Scientific, 2017)
"This review volume is motivated by the recent discovery of high-energy astrophysical neutrinos by IceCube. The aim of the book is to bring together chapters on the status of current and future neutrino observatories with chapters on the implications and possible interpretations of the present observations and their upper limits. Each chapter is a mini-review of one aspect of the subject by leading experts. Taken together, the chapters constitute an up-to-date review of high-energy astrophysical neutrinos and their potential sources"...